A New Proposal for OFCC-based Instrumentation Amplifier - Deva Nand; Neeta Pandey (Institute of Advanced Engineering and Science, 2017)
This contribution puts forward a new voltage mode instrumentation amplifier (VMIA) based on operational floating current conveyor (OFCC). It presents high impedance at input terminals and provides output at low impedance making the proposal ideal for voltage mode operation. The proposed VMIA architecture has two stages - the first stage comprises of two OFCCs to sense input voltages and coverts the voltage difference to current while the second stage has single OFCC that converts the current to voltage. In addition it employs two resistors to provide gain and imposes no condition on the values of resistors. The behavior of the proposed structure is also analyzed for OFCC non idealities namely finite transimpedance and tracking error. The proposal is verified through SPICE simulations using CMOS based schematic of OFCC. Experimental results, by bread boarding it using commercially available IC AD844, are also included.